Perception in Krashen's Monitor Utilization and the Learners' English-Speaking Performance - Lovely Jean C. Caratiquit; Kevin D. Caratiquit; Mark John M. Tamanu (Journal of English as A Foreign Language Teaching and Research, 2022)
Speaking of oral communication has frequently been labeled unfavorable to people because it requires confidence and courage. Thus, it appears to be one of the most challenging learning skills, requiring practice and exposure. This study aimed to investigate the relationship between Senior High School learners' level of performance in spoken discourse and their dominant monitor performance. The study employed a descriptive-correlational research design with 156 respondents selected through stratified random sampling. Recognizing and understanding Senior High School students' monitor performance was expected to motivate teachers to address the root cause of the problem, resulting in more proficient and communicative second language use. The findings disclosed that monitoring performance is crucial in determining the level of performance of learners in spoken discourse. A firm grasp of the English language, including its grammar and vocabulary components, effective discourse management, pronunciation, and interactive communication, are critical components in developing learners' speaking abilities. Additionally, this study revealed that those enrolled in the academic track are proficient at communicating, which explains why most are labeled optimal monitor users. In this regard, they use their information appropriately to strike a balance between self-correction and fluency, ensuring that error repair does not become a barrier to communication. Future recommendations were also discussed in this paper.